STUDI LITERATUR: PENERAPAN KONSEP MEKANIKA LAGRANGE PADA KEHIDUPAN SEHARI-HARI - Rahmah, Arina Alfa; Akhdania, Mahsa; Setiaji, Bayu (Charm Sains: Jurnal Pendidikan Fisika, 2024)
The application of mechanical concepts to everyday life is important in understanding the physical phenomena that occur. One branch of physics is mechanics which studies the behavior of objects influenced by force and displacement. In complex situations, many variables can be involved in the solution, so it is necessary to involve mathematical methods using the Lagrange equation. This article explains the application of Lagrange's equation in various systems such as pulleys, levers, oscillations, and double pendulum systems that are often encountered in everyday life. In addition, this article provides examples of tools encountered in daily activities that use the application of the Lagrange equation. The method used in collecting data for this article is a literature study method using 10 articles relevant to the theme. It is hoped that this article will be able to provide readers with an overview and understanding of concepts regarding Lagrange mechanics, as well as being able to provide concrete examples of real applications of physical theory in real life.